VD_FINDINFO HC / 2022 / 733 vom 5. Oktober 2022 - VD Tribunal cantonal (2022)
APPRÉCIATION DES PREUVES, TÉMOIN, CONTRAT DE TRAVAIL, RÉSILIATION ABUSIVE, MOTIF, INDEMNITÉEN GÉNÉRAL | 335 al. 1 CO, 336 CO, 336a al. 2 CO, 157 CPC (CH), 169 CPC (CH)